Developing Partnerships to Acquire Impact: The Role of Three Regional Centres’ Capacity Building Efforts for ODL Adoption in the Emerging World - Kirk Perris (Commonwealth of Learning, 2021)
Partnerships are central to the awareness, implementation and development of open and distance learning (ODL). It is an attribute that is distinct in the higher education sector, where ODL has made a large footprint by dispelling the notion that university enrolment is reserved for a narrow and elite demographic. The Commonwealth of Learning (COL) operates to advance the uptake of ODL amongst the 54 member states of the Commonwealth. COL leverages its work through various channels, and the COL Regional Centres play a pivotal role as partners to COL and, in turn, to acquire new partners that may benefit from COL’s technical expertise. The Regional Centres, strategically located across the Commonwealth, engage primarily in capacity building for ODL. Their constituents include governments, institutions, and individual learners. This paper explores the role of COL Regional Centres to grow existing partnerships and to form new ones in the pursuit of ODL expansion. The formation of partnerships is understudied in the ODL space, yet it has been pivotal in augmenting the visibility and importance of ODL around the world. Drawing on data from an evaluation of three COL Regional Centres conducted at the end of 2019, and reporting on follow-up activities to the mid-point of 2021, this paper highlights how the RCs are achieving their mandate to engage partners and, in the process, have achieved short- and long-term outcomes since 2018. Findings provide insight into the effectiveness of RC activities, relative to the number of institutions and individuals reached, complemented with inputs from RC stakeholders, mostly comprised of RC staff. Recommendations are offered, with the paper positing that the role of the Regional Centres should continue and expand to other areas of the Commonwealth premised on their ability to build and sustain partnerships through capacity building efforts.